Skin diseases in children in Eastern Turkey - Saraçlı, Teoman (The Turkish Journal of Pediatrics, 1971)
The incidences and types of skin diseases of 2,800 Turkish children seen in a three year period were reported. Fungal and bacterial infections of the skin were found in about half of the cases with tinea capitis (28.45 per cent) and primer pyodermas (16.09 per cent). One third of tinea capitis cases were favus. The high incidence of infectious diseases of the skin in children in Eastern Turkey was concluded to be due to poor socio-economic situation of this part of Turkey.